Unwanted taxpayers: Who is good at holding back reintegration research? - Paszti, Peter Gergely (Archives of Business Research, 2021)
While a relatively large amount of research is being conducted in prisons around the world, the number of searches allowed in penitentiary institutions in Hungary is very low. The problem is not only with the number of researches allowed, but also that in many cases the researcher is forced to make serious trade-offs to obtain a permit. And even if that wasn’t enough to get the researcher to refrain from doing his or her research, the penitentiary is constantly making it harder to complete it. In this short paper, I would like to show how my reintegration research has been hampered. It is as if the goal is to prevent convicts from receiving help for a successful reintegration.